Electrochemical- and mechanical stability of catalyst layers in anion exchange membrane water electrolysis. (22nd January 2022) - Mayerhöfer, Britta; Speck, Florian D.; Hegelheimer, Manuel; Bierling, Markus; Abbas, Dunia; McLaughlin, David; Cherevko, Serhiy; Thiele, Simon; Peach, Retha
Abstract: Anion exchange membrane (AEM) water electrolysis is considered a promising solution to future cost reduction of electrochemically produced hydrogen. We present an AEM water electrolyzer with CuCoOx as the anode catalyst and Aemion as membrane and electrode binder. Full cell experiments in pure water and 0.1 M KOH revealed that the optimum binder content depended on the type of electrolyte employed. Online dissolution measurements suggested that Aemion alone was not sufficient to establish an alkaline environment for thermodynamically stabilizing the synthesized CuCoOx in a neutral electrolyte feed. A feed of base is thus indispensable to ensure the thermodynamic stability of such non-noble catalyst materials. Particle loss and delamination of the catalyst layer during MEA operation could be reduced by employing a heat treatment step after electrode fabrication. This work summarizes possible degradation pathways for low-cost anodes in AEMWE, and mitigation strategies for enhanced system durability and performance. Graphical abstract: Image 1 Highlights: Implementation of CuCoOx -based anode electrodes for AEMWE. Evaluation of AEMWE-performance in 0.1 M KOH and pure water feed. Online SFC-ICP-MS dissolution studies with varying binder content and feed pH. Particle detachment can be mitigated by heat treating the electrode.